In-Service Infant Teachers Re-Envision Their Practice Through a Professional Development Program. Issue 1 (2nd January 2018) - Loizou, Eleni; Recchia, Susan L.
ABSTRACT: Research Findings : Most infant teachers have been prepared to be early childhood educators with minimal theoretical or practical exposure to infancy. This study highlights the outcomes of a professional development program (PDP) designed to support a group of infant teachers who lacked specific infancy preparation to re-envision their roles. Data sources included videotapes, focus groups, conversational interviews, reflective journaling, and artifacts. A PDP, tailored to the needs of the teachers, was developed in process in response to the outcomes of each step of the study. Findings highlight how teachers' existing beliefs inform current practice, teachers gain insight through new PDP strategies, and teachers' reflections on routines contribute to effective practice. Practice or Policy : Our PDP provided opportunities for reflection and pedagogical challenges as a means of creating space for educators to build a more grounded infant teacher identity. Implications of these findings are discussed in relation to infant teacher preparation and in-service training.